Awareness Analysis of Batik Craftsmen Regarding the Toxic and Hazardous Waste of the Batik Industry in Kampung Batik Laweyan (Case Study: Afina Batik) - Hashfi Hawali Abdul Matin; Muhammad Nur Sulton; Mochamad Erwantyo Nugroho; Murni Nurwulandari; Nurma Chandrasari; Rinoa Salsabila Izdihar; Zuhro Ainaya Risyafa (Diponegoro University, 2022)
The Batik industry is one of the industrial sectors that has an important role in improving the economy. As time goes by, the demand for batik is increasing. Not only favored by adults and the upper class, but batik is also increasingly favored by the youngsters. Therefore, batik industry craftsmen continue to follow technological developments in order to be able to meet the demand for batik, as in the batik industrial area of Kampung Batik Laweyan. Some of the equipment used is still relatively simple, but the use of chemicals has been carried out for quite a long time because the price of batik materials continues to increase. In fact, if the industrial waste is not handled properly, it can pollute the river. This shows that some batik industry perpetrators do not yet have a full level of awareness and responsibility for the output of batik making. Therefore, comprehensive research is needed on toxic and hazardous waste management in order to determine the perception of craftsmen towards toxic and hazardous waste and increase the awareness of craftsmen towards toxic and hazardous waste. Based on research conducted at Afina Batik using a combination of quantitative and qualitative approaches, information was obtained that some craftsmen did not know the types and dangers of chemical waste produced. In fact, there are chemicals used in the coloring process, such as napthol and chrome soga, which pose a risk of danger.